NORMATIVE CONDITIONS FOR THE DEVELOPMENT OF INNOVATION COMMERCIALIZATION INFRASTRUCTURE: EUROPEAN EXPERIENCE AND PROBLEMS - A. I. Kiselevich (Цифровая трансформация)
The article is devoted to the analysis of the process of commercialization of the innovations in the Republic of Belarus. The author analyzes the experience of European countries in the field of innovative development, as well as highlights a number of advantages received by the countries of the European Union. Also in the article are listed the normative legal documents defining the process of commercialization of innovations in the Republic of Belarus. The goal of improving the process of commercializing the results of scientific activity is to increase the competitiveness of the national economy, increase the number of scientific research proposed for financing, and accelerate the process of innovative development of the state. The author considers the benefits that states receive in the effective implementation of the process of commercialization of innovations. The article also draws attention to problems in the field of innovation development infrastructure. Conclusions were drawn with an emphasis on problem issues in the field of commercialization of innovations.